T Allele of FOXO3 rs2802292 Increases CCL2 Concentration and Slightly Decreases TGF-β Concentration in Indonesian Elderly - Nurfiyana, Wahyu; Iswanti, Febriana Catur; Hardiany, Novi Silvia (Molecular and Cellular Biomedical Sciences, 2024)
Background: Cellular senescence and the senescence-associated secretory phenotype (SASP) are pivotal factors influencing aging and age-related diseases. SASP secretes cytokines, chemokines, metalloproteinases, and growth factors that cause chronic inflammation. C-C ligand 2 (CCL2) and transforming growth factor-beta (TGF-β) are SASP markers secreted by senescent cells. This study investigated the relationship between the FOXO3 variant rs2802292 and SASP markers, focusing on CCL2 and TGF-β.Materials and methods: A cross-sectional study involving 72 elderly individuals from Jakarta was conducted. A sandwich enzyme-linked immunosorbent assay (ELISA)was used to quantify CCL2 and TGF-β concentrations. Random blood glucose, blood pressure, and FOXO3 rs2802292 genotyping data were obtained from a previous study. Differences in CCL2 and TGF-β concentrations between genotype groups were analyzed using one-way ANOVA and the Kruskal-Wallis test. Meanwhile, differences in CCL2 and TGF-β concentrations between allele groups were analyzed using the Mann-Whitney test.Results: The CCL2 and TGF-β concentrations of the subjects were 66.5 (10.58-190.9) pg/mL and 6,319 (2,379-13,846) pg/mL, respectively. There were significant differences in CCL2 concentrations among the FOXO3 rs2802292 genotypes (p=0.041). However, there were no significant differences in TGF-β concentrations among FOXO3 rs2802292 genotypes (p=0.955). Subjects with the G allele had significantly lower CCL2 concentrations compared with those with the T allele (p=0.033). TGF-β concentrations did not significantly differ between G and T alleles (p=0.771).Conclusion: CCL2 concentrations are associated with the FOXO3 variant rs2802292 in the elderly population. The T allele of FOXO3 rs2802292 increased CCL2 concentration and slightly decreased TGF-β concentration in elderly individuals.Keywords: aging, SASP, CCL2, TGF-β, SNP, FOXO3, rs2802292